2019
DOI: 10.1093/dote/doz093
|View full text |Cite
|
Sign up to set email alerts
|

Vascular pressure bands on high-resolution esophageal manometry with impedance studies

Abstract: Horizontal pressure bands on high-resolution esophageal manometry with impedance (HREMI) tracings are often seen and thought to be due to cardiovascular structures compressing the esophagus. The aim of this study was to determine the prevalence and location of vascular pressure bands on HREMI studies and correlate these pressure bands to bolus clearance. HREMI studies in supine and upright positions from patients and normal volunteers were reviewed. Pressure bands were defined as bands of horizontal pressure g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Although there was also delayed bolus transit, it is not clear whether this impedance abnormality was caused by DL. Horizontal pressure bands from cardiopulmonary structures are frequently found in both patients with dysphagia and healthy volunteers 9,13 . These vascular bands have been shown to sometimes impair esophageal bolus transit 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there was also delayed bolus transit, it is not clear whether this impedance abnormality was caused by DL. Horizontal pressure bands from cardiopulmonary structures are frequently found in both patients with dysphagia and healthy volunteers 9,13 . These vascular bands have been shown to sometimes impair esophageal bolus transit 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Horizontal pressure bands from cardiopulmonary structures are frequently found in both patients with dysphagia and healthy volunteers 9,13 . These vascular bands have been shown to sometimes impair esophageal bolus transit 13 . In addition, he has pronounced globus sensation, which may be due to his elevated resting UES pressure 14 and his DL.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular bands, also termed pulsatile pressure zones, vascular pressure bands, or horizontal pressure bands, identified during HRM occur frequently secondary to esophageal compression with abnormal vasculature, or cardiomegaly [1]. Previous studies identified that up to 56% of the HRM studies detected vascular bands [1][2][3]; moreover, the aortic arch, the aberrant subclavian artery and left atrium were categorized as the most implicated cardiovascular structures resulting in pressure bands [2]. While the clinical significance of vascular bands remains uncertain, they have been postulated to cause dysphagia in patients with additional underlying risk factors, such as, advanced age, atherosclerosis, and valvular heart disease [2].…”
Section: Image Of the Issuementioning
confidence: 99%